A Real-Time NMPC Guidance Law and Robust Control for an Autonomous Surface Vehicle. Issue 16 (2021) - Collado-Gonzalez, Ivana; Gonzalez-Garcia, Alejandro; Sotelo, Carlos; Sotelo, David; Castañeda, Herman
Abstract: This paper presents a path following control scheme for an autonomous surface vehicle under uncertainties and external disturbances. A guidance scheme based on nonlinear model predictive control takes into consideration the sideslip angle to overcome disturbances and generates the heading reference signal. The high-performance software package acados is used for solving the optimal control problem online. A dynamic controller based on adaptive sliding mode control presents robustness against external disturbances and uncertainties, driving the surge speed and heading dynamics. The control scheme is compared against a line-of-sight-based approach with the same dynamic controller to demonstrate the improvement of the proposed approach, including increased robustness and accuracy. Real-time simulation results show the efficiency, robustness, and feasibility of the proposed approach.